The Effect of Service Quality, Price, and Product Quality on Customer Satisfaction at Kana Eatery Coffe Kediri - Salsabillah, Natasya Firmanda; Ratnanto, Sigit (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This case aims determine factors that affect customer satisfaction. Design/Method/Approach : This case uses quantitative research methods. The research technique research is causality research questionnaires survey research methods, which are part of quantitative research. The population used all customers visit and products more than once at Kana Eatery Coffee Kediri. The sampling method applied in this case is non-probability sampling with an accidental sampling approach. Research Finding : Researchers found problems related to service quality, price, and product quality. Theoretical contribution/Originality : Coffee Shop is a place that is familiar to the community. Coffee shops are not only used for eating/drinking, but can also be used as a place to relax and gather with family and friends. Practitionel/Policy implication : The results of this study indicate that service quality partially has no effect on customer satisfaction. Price partially affects customer satisfaction. Product quality partially has no effect on customer satisfaction. Service quality, price, and product quality simultaneously affect customer satisfaction. Research limitation : In the data collection process, the information submitted by respondents through questionnaires often does not fully reflect their original opinions. This can occur due to differences in thinking, perception, and understanding between respondents, as well as other factors such as the level of honesty when filling out the questionnaire.